2007
DOI: 10.2478/s11686-007-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-embryonic development and ultrastructural characteristics of the polycephalic larva of Taenia parva Baer, 1926 (Cyclophyllidea, Taeniidae)

Abstract: Post-embryonic development and fully-formed polycephalic larvae of Taenia parva Baer, 1926 were examined by light (LM) and transmission electron microscopy (TEM). Three developmental stages were recognised: (1) an early stage of exogenous budding at the surface of the central vesicle; (2) a stage of polycephalic cyst development accompanied by segmentation of the growing larval strobile and an obvious decrease in the size of the central vesicle; (3) fully-formed larval strobile and invaginated scoleces. In ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…The second Taeniidae larva (Coenostrobilocercus) of Taenia sp., found in the two M. libycus of Dghoumes, is similar to that of T. parva Baer, 1926, previously detected by Campana-Rouget (1950 and Dollfus and Saint-Girons (1958) in the abdominal cavity of the wood mouse (Apodemus sylvaticus) from the French Eastern Pyrenees; then Bernard (1963) and more recently Swiderski et al (2007) found the same larval stages in the same rodent in Tunisia and the Iberian Peninsula, respectively. However, this parasite is known to be very specific in terms of both the definitive host and the intermediate host; the first being the common Genet (Genetta genetta) that lives in our study areas but seems to be very rare, and the second being the wood mouse.…”
Section: Discussionsupporting
confidence: 81%
“…The second Taeniidae larva (Coenostrobilocercus) of Taenia sp., found in the two M. libycus of Dghoumes, is similar to that of T. parva Baer, 1926, previously detected by Campana-Rouget (1950 and Dollfus and Saint-Girons (1958) in the abdominal cavity of the wood mouse (Apodemus sylvaticus) from the French Eastern Pyrenees; then Bernard (1963) and more recently Swiderski et al (2007) found the same larval stages in the same rodent in Tunisia and the Iberian Peninsula, respectively. However, this parasite is known to be very specific in terms of both the definitive host and the intermediate host; the first being the common Genet (Genetta genetta) that lives in our study areas but seems to be very rare, and the second being the wood mouse.…”
Section: Discussionsupporting
confidence: 81%
“…The morphology of the metacestodes from Taenia spp. can be remarkably varied, including large bladders with a single scolex (cysticercus), with many invaginated scoleces (coenurus), or with many externally protruding scoleces (‘polycephalic larvae’) [ 17 , 64 , 65 ], but in all cases the scolex develops towards the exterior of the bladder (exogenous development). Asexual formation of many scoleces is found in many basal taeniid lineages, suggesting that it was present in the last common ancestor of the family, but homology of asexual reproduction in taeniids is controversial [ 65 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once the development of the rostellum and the suckers is complete, the scolex invaginates into the posterior body, which is now only connected to the brood capsule by a thin stalk (however, the invagination of the scolex before development is completed has also been described [8,11]). The formation of multiple protoscoleces within each cyst results in asexual multiplication in the intermediate host, a process that is rare in cestodes but relatively common within the family Taeniidae (genera Taenia and Echinococcus [11-15]).…”
Section: Introductionmentioning
confidence: 99%